Asp J Pediatrics Child Health 2020
DOI: 10.36502/2020/asjpch.6150
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cross-Sectional Pharmacovigilance Study of Medication Errors in Children and Adults in Community-Based Hospitals

Abstract: Objective: To compare medication errors that reached pediatric and adult patients during hospitalization. Methods: Observational, non-experimental, cross-sectional study from January 2011 to March 2015 at two community-based, teaching hospitals. Results: Over a 4-year period, there were 4.2 and 13.3 million doses dispensed in pediatrics and adults, respectively. Less than 0.25% of doses dispensed contributed to medication errors, with 9.6% of these medication errors reaching patients and 0.04% causing harm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…33 Recent estimates also highlight this issue, whereby administration errors accounted between 42.5% and 54% of pediatric medication errors. 14,15 Of interest, Kaushal et al found that harmful errors occurred most commonly at the drug administration stage by parents. 34 Interventional studies in hospital medication administration errors explored barcode medicine administration, electronic prescribing, education and training, use of smart pumps, and standard concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Recent estimates also highlight this issue, whereby administration errors accounted between 42.5% and 54% of pediatric medication errors. 14,15 Of interest, Kaushal et al found that harmful errors occurred most commonly at the drug administration stage by parents. 34 Interventional studies in hospital medication administration errors explored barcode medicine administration, electronic prescribing, education and training, use of smart pumps, and standard concentration.…”
Section: Discussionmentioning
confidence: 99%
“…10 Patterns of medication errors in pediatrics are understudied in the hospital and community settings. 14,15 Besides, using information from studies conducted on adults may be of limited value, since medication errors most likely differ between the two populations. 16,17 Exploring specific patterns of medication errors in pediatrics compared with adults could enhance our understanding of this complex problem in pediatrics and inform targeted efforts to enhance patient safety.…”
Section: Introductionmentioning
confidence: 99%